Primary School Teachers' Uptake of Professional Readings: Understanding the Factors Affecting Teachers' Learning - Margaret Clare Kitchen; Maree Jeurissen; Susan Gray (New Zealand Journal of Teachers' Work)
Professional reading is a core source of input in teacher professional development. This article describes 47 primary school teachers' reports of their professional reading both in their schools and during the first year of a university TESOL (Teaching English to Speakers of Other languages) in-service qualification. One third of these teachers are bilingual. Both motivation and engagement are explored and vignettes of two bilingual teachers illustrate these factors. The findings show the frequency of participation in professional learning through professional readings is beneficial but low, however teacher professional reading attitudes are dynamic, the variables being relevancy and agency.